2022
DOI: 10.3390/ijerph19169796
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sustainable Communication Patterns during the Telework Period in Western Romanian Corporations

Abstract: The research was conducted in a particular context, the recent pandemic. It is a comparative study of the methods and quality of communication in global companies between 2021 and 2022. The corporations involved in the research are important providers of flexible production, quality, and logistics solutions that cover customers’ real needs. They are active in the automotive industry and units involved in mass production in the electronics industry, household appliances, and cosmetics industries. In their case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…In recent years, academic research into the tools, platforms and cybersecurity issues associated with telework has grown in importance. Some studies focus on the technological requirements, digital tools or communication platforms needed to ensure effective teleworking (Martin et al ., 2022; Ţigan et al ., 2022). Because telework relies heavily on technology and infrastructure, the results of our study demonstrated the need to change the conditions related to the use of technologies, and their positive and significant effect on the use of telework.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…In recent years, academic research into the tools, platforms and cybersecurity issues associated with telework has grown in importance. Some studies focus on the technological requirements, digital tools or communication platforms needed to ensure effective teleworking (Martin et al ., 2022; Ţigan et al ., 2022). Because telework relies heavily on technology and infrastructure, the results of our study demonstrated the need to change the conditions related to the use of technologies, and their positive and significant effect on the use of telework.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%